Growth and yield of cowpea as influenced by nitrogen and phosphorus levels on medium black soils of Gujarat - Verma, H.P.; Chovatia, P.K.; Sharma, Seema; Shivran, A.C. (Annals of Agricultural Research, 2016)
A field experiment was conducted during kharif 2012 on medium black soils of Gujarat to the study the effect of nitrogen and phosphorus levels on growth and yield of cowpea. The experiment consisted of four nitrogen (N) levels (control, 20, 30 and 40 kg N/ha) and four phosphorus (P2O5) levels (control, 40, 60 and 80 kg P2O5/ha) thereby making sixteen treatment combinations tested in factorial randomized block design with three replications. Application of nitrogen and phosphorus @ 40 and 80 kg/ha resulted in maximum and significantly higher plant height, dry matter accumulation, number of branches per plant, chlorophyll content, total & effective and fresh & dry weight of nodules per plant, seed and stover yield and remained at par with 20 & 30 kg N/ha and 40 & 60 kg P2O5/ha over control. The combined application of nitrogen and phosphorus @ 20 kg and 40 kg P2O5/ha was found significantly better in terms of seed and stover yield over rest of the treatments.